Anthracnose Fruit Rot of Chilli (Capsicum Annum L.): Some Aspects of its Etiology, Epidemiology and Control in Peninsular Malaysia - Mah, Shook Ying (1987)
Anthracnose fruit rot is a serious limiting factor in the production and yield of fresh chillies (Capsicum annuum L.) in Peninsular Malaysia. Isolates obtained from diseased chilli fruits collected in various localities in the country yielded the fungus, Colletotrichum capsici (Syd.) Butler & Bisby. Pathogenicity studies on mature chilli fruits confirmed that C. capsici could produce typical elliptical or oblong straw-coloured lesions on the fruit surface with subsequent development of black acervuli in concentric rings. Comparison of isolates on potato dextrose agar showed that all the isolates were relatively similar in cultural and morphological characteristics. Germination of conidia occurred 3-4 hours after plating on chilli agar medium. Branching of germtubes occurred between 16-24 hour s after germination. The fungus grew over a wide range of hydrogen-ion concentrations (between pH 3.0 and pH 10.0) with optimum between pH 7.0 and pH 9.5. Acervuli formation and development was more evident on alkaline medium than on acidic medium. Optimum temperature for mycelial growth was between 25˚C and 32˚C. The minimum and maximum temperatures for visible growth were l0˚C and 45˚C , respectively.